Biología floral de Passiflora foetida (Passifloraceae) - Amela García, María T; Hoc, Patricia S (Revista de Biología Tropical, 1998)
A reproductive experiment shows that Passiflora foetida is autocompatible. Observations of floral characteristics and visitors during anthesis, plus the analysis of pollen alIowed identification of floral syndrome (melittophily) and functions for each visitor. Anthesis occurs from 6 to 11 A M. Three floral phases were identified: 1) stigmas aboye anthers, 2) stigmas at anther level, 3) stigmas aboye anthers; radii, petals and sepals become incurved. The stigmas are receptive during the whole anthesis. The concentration of sugars in nectar is 34 %. The predominant color in the visible spectrum is white. The stamens and the gynoecium contrast against the limen and androgynophore in the UV spectrum, maybe a nectar guide. Three species of hymenopterans are the most frequent and constant visitors: Ptiloglossa tarsata (Colletidae) always contact the anthers and the stigmas while sucking nectar, carry a high percentage of P. ¡oetida pollen and visit flowers in phases l and 2; they can be considered the main pollinators. Pseudaugochloropsis sp. ( Halictidae) rarely contact anthers and stigmas while puncturing the limen to access nectar, and visít flowers in phases 2 and 3; they are nectar robbers tha! rarely pollinate. Augochlorella sp. ( Halictidae) collect pollen without touching the stigmas and visit flowers in phases 2 and 3; they are pollen thieves.